Avoiding Drug Resistance by Substrate Envelope-Guided Design: Toward Potent and Robust HCV NS3/4A Protease Inhibitors - Ashley N. Matthew (American Society for Microbiology, 2020)
ABSTRACT Hepatitis C virus (HCV) infects millions of people worldwide, causing chronic liver disease that can lead to cirrhosis, hepatocellular carcinoma, and liver transplant. In the last several years, the advent of direct-acting antivirals, including NS3/4A protease inhibitors (PIs), has remarkably improved treatment outcomes of HCV-infected patients. However, selection of resistance-associated substitutions and polymorphisms among genotypes can lead to drug resistance and in some cases treatment failure. A proactive strategy to combat resistance is to constrain PIs within evolutionarily conserved regions in the protease active site. Designing PIs using the substrate envelope is a rational strategy to decrease the susceptibility to resistance by using the constraints of substrate recognition. We successfully designed two series of HCV NS3/4A PIs to leverage unexploited areas in the substrate envelope to improve potency, specifically against resistance-associated substitutions at D168. Our design strategy achieved better resistance profiles over both the FDA-approved NS3/4A PI grazoprevir and the parent compound against the clinically relevant D168A substitution. Crystallographic structural analysis and inhibition assays confirmed that optimally filling the substrate envelope is critical to improve inhibitor potency while avoiding resistance. Specifically, inhibitors that enhanced hydrophobic packing in the S4 pocket and avoided an energetically frustrated pocket performed the best. Thus, the HCV substrate envelope proved to be a powerful tool to design robust PIs, offering a strategy that can be translated to other targets for rational design of inhibitors with improved potency and resistance profiles. IMPORTANCE Despite significant progress, hepatitis C virus (HCV) continues to be a major health problem with millions of people infected worldwide and thousands dying annually due to resulting complications. Recent antiviral combinations can achieve >95% cure, but late diagnosis, low access to treatment, and treatment failure due to drug resistance continue to be roadblocks against eradication of the virus. We report the rational design of two series of HCV NS3/4A protease inhibitors with improved resistance profiles by exploiting evolutionarily constrained regions of the active site using the substrate envelope model. Optimally filling the S4 pocket is critical to avoid resistance and improve potency. Our results provide drug design strategies to avoid resistance that are applicable to other quickly evolving viral drug targets.